Growth Performance, Feed Intake, Sensory Attributes, and Blood Profile of Male Guinea Fowls Fed with Different Diets: Growth Performance, Feed Intake, Sensory Attributes, and Blood Profile of Male Guinea Fowls - Oluwadele, Joshua (Universitas Airlangga, 2025)
This study evaluates the growth performance, feed intake, sensory attributes, and blood profile of male guinea fowls (Numida meleagris) fed different cereal-based diets. A total of 100 male guinea fowls were randomly assigned to three dietary treatments containing maize, millet, or sorghum as primary energy sources. The experiment lasted eight weeks, with data collected on body weight, feed conversion ratio (FCR), meat quality, and blood parameters.Results showed that millet-based diets significantly improved growth performance during the starter phase (P < 0.05), with higher body weight (135.75 g at 4 weeks) and average daily gain (3.95 g/day) compared to maize (109.95 g, 3.00 g/day) and sorghum (128.10 g, 3.65 g/day).** Feed intake was highest in millet-fed birds**, though differences were not statistically significant (P > 0.05). Feed conversion efficiency was slightly better for millet-fed keets (FCR = 3.17) compared to sorghum (3.47) and maize (3.67).Sensory evaluation revealed that millet-fed guinea fowls had slightly superior flavor, juiciness, and tenderness scores, though variations across diets were not statistically significant (P > 0.05). Blood profiles remained within normal ranges, indicating that all diets supported adequate health.These findings suggest that millet-based diets optimize early growth and meat quality in guinea fowls, making them a cost-effective alternative to maize in poultry nutrition. Future research should explore long-term economic benefits and the feasibility of integrating millet into large-scale commercial feed formulations.